Perancangan Sistem Informasi Penggajian Di Artnang Studio Berbasis Website - Diki Setiawan; Chairullah Naury; Kresno Ario Triwibowo (Politeknik Harapan Bangsa Surakarta, 2024)
Artnang Studio is a company in the printing services industry. The current payroll data management system at Artnang Studio remains quite basic. Employee data is still recorded manually in a designated book each month, and salary reports are provided in a traditional format. This conventional system creates several issues in the payroll process, including data inconsistency, which can lead to duplicate payroll records. Additionally, retrieving payroll information is time-consuming since data is only stored as an archive, and data security remains insufficient under the current system. Based on these background issues, this study addresses the problem of “How to design a web-based payroll system for Artnang Studio.” The study focuses specifically on the payroll process, managing data such as base salary, attendance, and overtime wages. The system is developed using PHP Native for programming and MySQL for database storage. The design methodology follows the Software Development Life Cycle (SDLC) with the Waterfall model. This study aims to create an application program to manage payroll data effectively at Artnang Studio, with the benefit of expediting the payroll reporting process. The outcome of this study is expected to provide a payroll system that assists with monthly salary reporting, especially for Artnang Studio.